Comparison of coated and uncoated trace elements on growth performance, apparent digestibility, intestinal development and microbial diversity in growing sheep - Zhou, Jia; Ren, Yifan; Wen, Xiao; Yue, Shuangming; Wang, Zhisheng; Wang, Lizhi; Peng, Quanhui; Hu, Rui; Zou, Huawei; Jiang, Yahui; Hong, Qionghua; Xue, Bai (Frontiers in Microbiology, 2022)
The suitable supplement pattern affects the digestion and absorption of trace minerals by ruminants. This study aimed to compare the effects of coated and uncoated trace elements on growth performance, apparent digestibility, intestinal development and microbial diversity in growing sheep. Thirty 4-month-old male Yunnan semi-fine wool sheep were randomly assigned to three treatments (n = 10) and fed with following diets: basal diet without adding exogenous trace elements (CON), basal diet plus 400 mg/kg coated trace elements (CTE, the rumen passage rate was 65.87%) and basal diet plus an equal amount of trace elements in uncoated form (UTE). Compared with the CON group, the average daily weight gain and apparent digestibility of crude protein were higher (P < 0.05) in the CTE and UTE groups, while there was no difference between the CTE and UTE groups. The serum levels of selenium, iodine and cobalt were higher (P < 0.05) in the CTE and UTE groups than those in the CON group, the serum levels of selenium and cobalt were higher (P < 0.05) in the CTE group than those in the UTE group. Compared with the CON and UTE groups, the villus height and the ratio of villus height to crypt depth in duodenum and ileum were higher (P < 0.05) in the CTE groups. The addition of trace minerals in diet upregulated most of the relative gene expression of Ocludin, Claudin-1, Claudin-2, ZO-1 and ZO-2 in the duodenum and jejunum and metal ion transporters (FPN1 and ZNT4) in small intestine. The relative abundance of the genera Christensenellaceae R-7 group, Ruminococcus 1, Lachnospiraceae NK3A20 group and Ruminococcaceae in ileum, and Ruminococcaceae UCG-014 and Lactobacillus in colon was higher in the CTE group that in the CON group. These results indicated that dietary trace mineral addition improved the growth performance and intestinal development, and altered the structure of intestinal bacteria in growing sheep. Compared to uncoated form, offering trace mineral elements to sheep in coated form had a higher absorption efficiency, however, had little effect on improving growth performance of growing sheep.